Fabricating an Interim Immediate Partial Denture in One Appointment (Modified Jiffy Denture). A Clinical Report. Issue 4 (20th December 2012) - Gooya, Ali; Ejlali, Massod; Adli, Amin Rezayi
Abstract An immediate denture is fabricated before all the remaining teeth have been removed. Its advantages include maintenance of a patient's appearance, muscle tone, facial height, tongue size, and normal speech and reduction of postoperative pain. The purpose of this study is to describe the use of a patient's fixed prosthesis for fabricating an interim immediate partial denture in one appointment. Occlusion, occlusal vertical dimension, and facial support are maintained during the healing period in this procedure.